The Influence of Dimensions Female Leadership Competencies To SMEs Performance - Prajawati, Maretha Ika; Nur Aisyah, Esy; Setiani, Setiani (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Improving female leadership will have a lasting impact on the development of future female leaders. With societal advancements, the knowledge and quality of female employee representatives have significantly improved, leading to increased effectiveness of female leaders. Female leadership is closely tied to company competitiveness and gaining a competitive advantage.Purpose: The aim of this study is to investigate the leadership of female SME owners by applying the hypothesis of competitiveness to analyze the leadership competencies that influence the competitiveness of SMEs.Design/methodology/approach: This research adopts a quantitative approach, focusing on SMEs in Batu City. Based on Slovin's formula, the sample size for this study was determined to be 100 respondents.Findings/Result: The research demonstrates that entrepreneurial competencies play a crucial role in business development and success, highlighting the importance of understanding the nature and role of competencies in SMEs. Strategic vision, operations management, professional knowledge, hands-on experience, and relationship building have a significant impact on performance.Conclusion: The rapid growth of SMEs clearly illustrates the importance of leadership in achieving success. However, while leadership is often seen as a personal attribute, and better leadership is believed to result from developing individual leader competencies, it is essential to explore the relationship between competence and leadership style.Originality/value (State of the art): This research emphasizes the importance of long-term growth over short-term profitability for SMEs. The capacity for long-term development is considered essential for SMEs, and this study investigates the impact of female leadership competencies on the growth and performance of SMEs. Keywords: strategic visions, operations management, professional knowledge, hand on experience, relationship building